2017
DOI: 10.3390/molecules22071153
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin and Flavonoids Do Not Share the Same Binding Region in Binding to the IIA Subdomain of Human Serum Albumin

Abstract: Human serum albumin (HSA) binds a variety of xenobiotics, including flavonoids and warfarin. The binding of another ligand to the IIA binding site on HSA can cause warfarin displacement and potentially the elevation of its free concentration in blood. Studies dealing with flavonoid-induced warfarin displacement from HSA provided controversial results: estimated risk of displacement ranged from none to serious. To resolve these controversies, in vitro study of simultaneous binding of warfarin and eight differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 48 publications
3
29
0
Order By: Relevance
“…The obtained results are in accordance with results obtained by Zsila et al [18] and Dufour and Dangles [7], as well as with the crystallographic structures obtained by Petitpas et al [34] and Yamasaki et al [35,36], stating that the binding site in the subdomain IIA of HSA is large enough to accommodate multiple ligands at the same time. This was also confirmed for the case of interactions between warfarin and quercetin [29]. The difference in QUE fluorescence is likely brought about either by (i) conformational changes within the ligand; (ii) potential changes in the size and shape of the IIA binding site caused by the presence of IND; or (iii) through the direct interaction of IND and QUE, which decreases QUE's rotational and translational freedom and consequently stabilizes the ternary HSA-IND-QUE complex.…”
Section: Simultaneous Binding Of Indomethacin and Quercetin To Hsasupporting
confidence: 64%
See 3 more Smart Citations
“…The obtained results are in accordance with results obtained by Zsila et al [18] and Dufour and Dangles [7], as well as with the crystallographic structures obtained by Petitpas et al [34] and Yamasaki et al [35,36], stating that the binding site in the subdomain IIA of HSA is large enough to accommodate multiple ligands at the same time. This was also confirmed for the case of interactions between warfarin and quercetin [29]. The difference in QUE fluorescence is likely brought about either by (i) conformational changes within the ligand; (ii) potential changes in the size and shape of the IIA binding site caused by the presence of IND; or (iii) through the direct interaction of IND and QUE, which decreases QUE's rotational and translational freedom and consequently stabilizes the ternary HSA-IND-QUE complex.…”
Section: Simultaneous Binding Of Indomethacin and Quercetin To Hsasupporting
confidence: 64%
“…Apart from the regular, competitive displacement interactions and non-interactions (e.g., warfarin-quercetin [29]), the obtained insight into the binding process suggests a third option for ligand-ligand interactions in a simultaneous binding to the same protein binding site, where one ligand increases the binding constant of the other ligand. At this moment, we are not aware of other studies that have reported similar results, which could have important consequences for the fate of xenobiotics inside the body.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Site II more actively binds indole and aromatic compounds, such as ibuprofen [ 36 ]. Warfarin and ibuprofen are routinely used to probe sites I and II, respectively [ 37 ]. As shown in Figure 7 and Table 6 , quenching of HSA fluorescence intensity by about 20% and a blue shift were also observed in all groups.…”
Section: Resultsmentioning
confidence: 99%